2017
DOI: 10.1002/ecs2.1737
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and regeneration dynamics ofQuercus variabilisalong latitudinal and longitudinal gradients

Abstract: Population structure and regeneration dynamics of Quercus variabilis along latitudinal and longitudinal gradients.Ecosphere 8(4):e01737. 10.1002/ecs2.1737Abstract. The upcoming climatic variability is expected to influence the population dynamics of tree species, but few empirical studies have been performed over broad geographical scales, which may be more convincing to address tree range shift under climate change. In the present study, the population structure and regeneration dynamics of Quercus variabilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 91 publications
(179 reference statements)
0
16
0
1
Order By: Relevance
“…Alternatively, other factors, such as recruitment limitation, rather than NSC at the north edges may contribute to the oak’s north-latitudinal limit formation. Our previous study found that the relative densities of seedlings of the species studied were significantly lower in the northern edge than in the core populations ( Gao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 80%
“…Alternatively, other factors, such as recruitment limitation, rather than NSC at the north edges may contribute to the oak’s north-latitudinal limit formation. Our previous study found that the relative densities of seedlings of the species studied were significantly lower in the northern edge than in the core populations ( Gao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 80%
“…Zhu, Lu, and Zhang (2014) reported that forest gaps augment the regeneration of woody plant species. Besides, local factors, soil and stand conditions play substantial role in regeneration dynamics (Gao et al, 2017). Tree species having no regeneration may be due to the availability of enough moisture content of the soil for the germination of seeds also reported by Tiwari, Rana, Krishan, Sharma, and Bhandari (2018).…”
Section: Discussionmentioning
confidence: 93%
“…According to species distribution models and field investigations, our previous work (Gao et al. , ), as well as that of Li and Zhang (), revealed that the distribution range of the Chinese cork oak may shrink and retreat under the expected climate warming. However, the growth response at their range limit is not yet understood.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies demonstrated that temperate and boreal tree species presented a growth increase toward the northern parts of the species range limits in the Northern Hemisphere (Jump , Sánchez‐Salguero et al , Gao et al. , ). However, there are still research gaps on how rising temperatures will affect tree growth under projected climatic conditions, especially the southern range limit in semiarid area.…”
Section: Introductionmentioning
confidence: 97%